Oxidative potential of ultraviolet‐A irradiated or nonirradiated suspensions of titanium dioxide or silicon dioxide nanoparticles on Allium cepa roots. (25th February 2014) - Koce, Jasna Dolenc; Drobne, Damjana; Klančnik, Katja; Makovec, Darko; Novak, Sara; Hočevar, Matej
Abstract The effect of ultraviolet‐A irradiated or nonirradiated suspensions of agglomerates of titanium dioxide (TiO2) or silicon dioxide (SiO2) nanoparticles on roots of the onion (Allium cepa) has been studied. The reactive potential of TiO2 nanoparticles, which have photocatalytic potential, and the nonphotocatalytic SiO2 nanoparticles with the same size of agglomerates was compared. The authors measured the activity of antioxidant enzymes glutathione reductase, ascorbate peroxidase, guaiacol peroxidase, and catalase as well as lipid peroxidation to assess the oxidative stress in exposed A. cepa roots. A wide range of concentrations of nanoparticles was tested (0.1–1000 µg/mL). The sizes of agglomerates ranged in both cases from 300 nm to 600 nm, and the exposure time was 24 h. Adsorption of SiO2 nanoparticles on the root surface was minimal but became significant when roots were exposed to TiO2 agglomerates. No significant biological effects were observed even at high exposure concentrations of SiO2 and TiO2 nanoparticles individually. Plants appear to be protected against nanoparticles by the cell wall, which shields the cell membrane from direct contact with the nanoparticles. The authors discuss the need to supplement conventional phytotoxicity and stress end points with measures of plant physiological state when evaluating the safety of nanoparticles. Environ Toxicol Chem 2014;33:858–867. © 2013 SETAC